Small amplitude rayleigh-lamb wave propagation in a finitely deformed viscoelastic dielectric elastomer (DE) layer. (January 2021) - Mohajer, Mohammad; Zhou, Jianyou; Jiang, Liying
Abstract: In recent years, Dielectric elastomers (DEs) have received much interest for the dynamics applications as waveguide. However, predicting the wave propagation behavior in a DE medium is very challenging due to the complexity of the problem, which involves the delicate interplay between electromechanical coupling, large deformation, and particularly the intrinsic material viscoelasticity. In this paper, by integrating the state-of-art finite-deformation viscoelasticity theory into the framework of small-amplitude wave propagation superimposed on a finitely deformed medium, the Rayleigh-Lamb wave propagation in a viscoelastic DE medium is investigated. Simulation results demonstrate the effects of material viscosity, status of relaxation, external electrical load, and mechanical pre-stretch on the dispersion behavior of the wave. It is found that for both purely elastic and viscoelastic DE media, waves with certain frequencies could be filtered by actively tuning the electrical loads. Moreover, some interesting findings conclude that the material viscoelasticity may cause some significant changes in the wave dispersion behavior. Therefore, incorporating the material viscosity in modeling DE waveguide is expected to provide more accurate prediction on their performance. This work will help to better understand the fundamentals of wave propagation in DE media and trigger more innovative and optimal design for DE waveguide.